2005
DOI: 10.1074/jbc.m409883200
|View full text |Cite
|
Sign up to set email alerts
|

The Expression of Intact and Mutant Human apoAI/CIII/AIV/AV Gene Cluster in Transgenic Mice

Abstract: The apoAI/CIII/AIV gene cluster is involved in lipid metabolism and has a complex pattern of gene expression modulated by a common regulatory element, the apoCIII enhancer. A new member of this cluster, apolipoprotein (apo) AV, has recently been discovered as a novel modifier in triglyceride metabolism. To determine the expression of all four apo genes in combination and, most importantly, whether the transcription of apoAV is coregulated by the apoCIII enhancer in the cluster, we generated an intact transgeni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
17
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(20 citation statements)
references
References 34 publications
3
17
0
Order By: Relevance
“…Downexpression of apoc3, but not apoa4, results from interference by the nearby neomycin resistance cassette (14,21). In contrast, apoa5 gene expression was found to be normal in Apoa1/c3/a4 mice (data not shown) and so likely in Apoa1 2/2 mutants, consistent with transgenic studies showing that the apoC-III enhancer regulates the expression of apoA-I, apoC-III, and apoA-IV but not apoA-V in vivo (36). These data demonstrate that Apoa1 2/2 mice are apoA-I/C-III-deficient and differ from Apoa1/c3/a4 2/2 mice mostly by the presence of apoA-IV.…”
Section: Discussionsupporting
confidence: 70%
“…Downexpression of apoc3, but not apoa4, results from interference by the nearby neomycin resistance cassette (14,21). In contrast, apoa5 gene expression was found to be normal in Apoa1/c3/a4 mice (data not shown) and so likely in Apoa1 2/2 mutants, consistent with transgenic studies showing that the apoC-III enhancer regulates the expression of apoA-I, apoC-III, and apoA-IV but not apoA-V in vivo (36). These data demonstrate that Apoa1 2/2 mice are apoA-I/C-III-deficient and differ from Apoa1/c3/a4 2/2 mice mostly by the presence of apoA-IV.…”
Section: Discussionsupporting
confidence: 70%
“…23 Mouse Breeding, Diet, and Analysis of Atherosclerotic Lesions PC Tg mice were crossed with ApoE-null mice to obtain PC Tg/ApoE-null mice and ApoE-null littermates, which were maintained on chow diet for 6 weeks and then switched to a Western diet containing 10% fat and 1.25% cholesterol to induce atherogenesis. En face aorta atherosclerotic lesions were analyzed as described.…”
Section: Construction Of Human Pon Cluster Transgenic Micementioning
confidence: 99%
“…A recent study showing that the APOC3-enhancer that affects expression of the APOA1, APOC3, and APOA4 genes does not up-regulate transcription of the APOA5 gene (Gao et al 2005) provided some insight into this issue, but several points remain uncertain. For example, it is unclear why the APOC3-enhancer is not able to act upon the APOA5-promoter that is just 35 kb away, when it is known that eukaryotic enhancers may exert their effects up to a distance of 100-kb (Zhao and Dean 2005).…”
Section: Discussionmentioning
confidence: 99%
“…In particular, the distal APOC3-enhancer can regulate tissue-specific expression of the three APOA1, APOA4, and APOC3 genes (Ogami et al 1990;Ktistaki et al 1994;Zannis et al 2001). A recent study found that this common enhancer did not regulate in vivo APOA5 expression (Gao et al 2005), which agrees with much lower plasma levels of apoAV compared to other apolipoproteins (O'Brien et al 2005). For example, plasma apoAV levels (24-406 lg/l) (O'Brien et al 2005) are 1,000-2,000-fold-lower than human apoCIII plasma concentrations (50-140 mg/l) (Marz et al 1987;Sakurabayashi et al 2001).…”
Section: Introductionmentioning
confidence: 99%